A Combination of Plastic and Swaddle in Controlling Hypothermia in Infant Transfer at Hospital - Ida Subardiah Pelitawati; Yuli Lestari; Dewi Yuliana; Gustop Amatiria (Poltekkes Kemenkes Tanjung Karang, 2025)
Premature and low birth weight babies are at risk of hypothermia admission, which is estimated at 39.8% of babies who arrive at the hospital shortly after referral. The handling of referral transfers of premature and low-birth-weight infants applies the principles of thermal care and comfort to maintain normothermia. This study aimed to evaluate the management of hypothermia in premature and low birth weight infants using a combination of plastic bags and swaddles. Controlling hypothermia admissions in infant transfer cases. The study used a nonequivalent control group design. The population in this study is premature and low birth weight infants. A total of 20 respondents were selected using the consecutive sampling technique. The research instrument was a hypothermia management observation sheet. The analysis used the T-test. The results showed a significant difference in body temperature between groups (p=0.000); there was a significant difference in body temperature between before and after (intervention p=0.002; control p=0.568). The combination of a plastic bag and a swaddle is safe to use in maintaining normal baby temperature during referral. This intervention is cost-effective, simple, and highly relevant, especially in facilities with limited resources.